The Effect of an Oxytocin Decision Support Checklist on Oxytocin Use and Maternal and Neonatal Outcomes: A Retrospective Cohort Study - Kandahari, Nazineen; Tucker, Lue-Yen; Raine-Bennett, Tina; Palacios, Janelle; Schneider, Allison N.; Mohta, Vanitha J. (American Journal of Perinatology, 2024)
Objective To assess the association between use of an oxytocin decision support checklist with oxytocin usage and clinical outcomes.Study Design We conducted a retrospective cohort study of patients with singleton gestations at 370/7 weeks or greater who received oxytocin during labor from October 2012 to February 2017 at an integrated community health care system during three exposure periods: (1) prechecklist; (2) after paper checklist implementation; and (3) after checklist integration into the electronic medical record (EMR). The checklist was a clinical decision support tool to standardize the dosing and management of oxytocin. Thus, our primary outcomes included oxytocin infusion rates and cumulative dose. Secondary outcomes included maternal and neonatal outcomes. We controlled for maternal risk factors with multivariable regression analysis and stratified by mode of delivery.Results A total of 34,269 deliveries were included. Unadjusted analyses showed that compared with prechecklist, deliveries during the paper and EMR-integrated periods had a lower cumulative dose (4,670 ± 6,174 vs. 4,318 ± 5,719 and 4,286 ± 5,579 mU, p < 0.001 for both), lower maximal infusion rate (9.9 ± 6.8 vs. 8.7 ± 5.8 and 8.4 ± 5.6 mU/min, p < 0.001 for both), and longer duration of oxytocin use (576 ± 442 vs. 609 ± 476 and 627 ± 488 minutes, p < 0.001 and p = 0.01, respectively). The unadjusted rates of cesarean, 5-minute Apgar <7, mechanical ventilation, and neonatal hospital length of stay were similar between periods. The adjusted mean difference in time from admission to delivery was longer during the EMR-integrated period compared with prechecklist (3.0 [95% confidence interval: 2.7–3.3] hours, p < 0.001).Conclusion Oxytocin checklist use was associated with decreased oxytocin use patterns at the expense of longer labor times. Findings were more pronounced with EMR integration.Key Points
Keywords: oxytocin; decision support; checklist; maternal outcomes; neonatal outcomes